2012
DOI: 10.4103/0019-509x.98930
|View full text |Cite
|
Sign up to set email alerts
|

Comparison study of clinicoradiological profile of primary lung cancer cases: An Eastern India experience

Abstract: SCC is the most common histological subtype of primary bronchogenic carcinoma. The relatively increased frequency of adenocarcinoma in our study as compared to other studies from India is probably due to higher proportion of nonsmokers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

19
34
7
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 19 publications
19
34
7
1
Order By: Relevance
“…We found the male/female ratio as 6.1/1. The male/female ratio in India has been found as 4.1/1, which is lower than the results in our study (Dey et al, 2012). In Japan the ratio is 2.8/1 (Kanematsu et al, 2010).…”
contrasting
confidence: 94%
See 3 more Smart Citations
“…We found the male/female ratio as 6.1/1. The male/female ratio in India has been found as 4.1/1, which is lower than the results in our study (Dey et al, 2012). In Japan the ratio is 2.8/1 (Kanematsu et al, 2010).…”
contrasting
confidence: 94%
“…The difference in the male female ratio of primary lung cancer among urban versus rural population was not significant (p=0.668). Similar results are reported in Eastern India in 2012 (Dey et al, 2012) Although central location is more often seen in squamous cell carcinoma and small cell carcinoma, peripheral location is seen in adenocarcinoma more frequently (Arınç et al, 2007). Our results were consistent with the literature.…”
supporting
confidence: 74%
See 2 more Smart Citations
“…Jindal et al [4] found that 14.6% of the patients being aged less than 41 years and Day et al found that 9.4% patients were ≤ 40 years of age. [5] Most of our patients (65%) belonged to rural area. This may be because most of the patients in our hospital comes from rural background and this may be just a reflection to the patient's profile of the hospital.…”
Section: Discussionmentioning
confidence: 86%